STP STRATEGY IN IMPROVING BRAND AWARENESS OF BU ENDAH'S TRADITIONAL SNACKS - zahwa audinar, aura; Nurzainul Hakimah, Ema (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research purposes : Increase brand awareness of Jajanan Bu Endah and formulate the right marketing strategy, especially in the STP aspect. Design/Method/Approach : The method used in this research is a qualitative method, while the type of research approach is phenomenology which focuses on individual life experiences. Research Findings :Mrs. Endah divides the segment with a primary focus on consumers aged 20-40 years who live in urban areas because they tend to like authentic and practical snacks. This target market can be reached through digital marketing, such as social media and collaboration with influencers. With positioning that emphasizes authentic taste, natural ingredients without preservatives, and environmentally friendly packaging, Mrs. Endah can present uniqueness that differentiates her products from modern snacks. Theoretical contribution/Originality : This research contributes to the development of STP strategies to increase brand awareness of Bu Endah's traditional snacks, both from a scientific and practical perspective. This research enriches the literature on the application of marketing strategies to local products with an approach that adapts to the characteristics of traditional and modern markets. Practitioner/Policy Implications : MSMEs like Mrs. Endah can utilize social media to reach a wider market segment. The use of premium raw materials and environmentally friendly packaging can be the main selling points. Collaboration with local influencers can strengthen the brand image as a high-quality traditional product. Research limitations : This study only focuses on one location (Kediri), so the results cannot be generalized to other areas with different market conditions and the data used is limited to interviews and observations in a small number of informants, so it does not provide a broad representation.